On contact umbolic hypersurface in O-pair space - Kriščiūnaitė, A. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Л. Крищунайте. О конткатных омбилических гиперповерхностях в пространстве O-пар A. Kriščiūnaitė. Apie kontaktinius umbilinius hiperpaviršius O-porų erdvėje